Effect of Cavity-Based Surface Geometry on Electromagnetic Wave Absorption in Radar Absorbing Materials: A Review - Nurhasmi (Pinisi: Physics Journal, 2026)
Radar Absorbing Materials (RAM) are critical components in stealth technology and Radar Cross Section (RCS) reduction. This review examines the effect of cavity-based surface geometry on electromagnetic wave absorption performance across the radar frequency range (1–40 GHz). The blackbody radiation analogy is adopted as a conceptual framework explaining how surface cavities trap electromagnetic waves via multiple reflections. Absorption performance is quantified using the reflection loss (RL) model derived from transmission line theory. The review covers hollow pyramidal absorbers (HPA), honeycomb microwave absorbers (HMA), honeycomb–hollow pyramid metastructures (HPS), corrugated structures, and gradient 3D-printed designs. The HPS achieves RL below −15 dB across 8–18 GHz at 5 mm thickness, while corrugated structures achieve −19.5 dB with 2.31–18 GHz bandwidth. Carbon-based wall materials (graphene, MXene, CNT) and magnetic materials (ferrite, hexaferrite) provide complementary permittivity and permeability values essential for impedance matching. However, studies independently isolating the cavity geometry contribution from material composition remain scarce. This review provides a systematic foundation for experimental research on cavity geometric parameters.